PENGARUH PENDIDIKAN PELATIHAN, MUSYAWARAH GURU MATA PELAJARAN TEKNIK OTOMOTIF DAN PENGALAMAN KERJA TERHADAP PROFESIONALISME GURU SMK SE KABUPATEN WONOSOBO (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
The research aims at finding out the Influence of Education and Training, The Automotive Engineering Teachers Association and Job experience to the professionalism of Vocational High School Teachers in Wonosobo Regency, both in state schools and private schools in Academic Year 2014/2015.The research is correlative in nature i.e. finding out the correlation of the variables shown by the correlation coefficient numbers. The data was taken from the population i.e. Automotive Engineering teachers united in the Automotive Engineering Teachers AssociationÂ  in Wonosobo Regency. The data was taken from the population of 73 people. The technique of collecting the data was using questionaire instrument. The technique of analyzing the data is using double regression technique with three predictors. Hypothesis test collectively used F test or ANAVA test continued by hypothesis test individually which used partial test. The data was tested with prerequisite test that is normality, linearity and multi co linearity test with the significant grade is 5%.Based on the research, it is concluded that: 1. Collectively, The education and training, the The Automotive Engineering Teachers Association and Job experience give a very significant Influence to the professionalism of Vocational High School Teachers in Wonosobo Regency with the Influence t effectiveness is 64,941%. 2. Separately, the education and training gives a positive and significant Influence towards the professionalism of Vocational High School in Wonosobo Regency with the Influence effectiveness is 42,169% .3. Separately, The Automotive Engineering Teachers Association and Job experience gives a positive and significant Influence towards the professionalism of Vocational High School teachers in Wonosobo Regency with the Influence effectiveness is 12,854%. 4. Separately, the job experience gives a positive and significant Influence to the professionalism of Vocational High School teachers in Wonosobo Regency with the Influence effectiveness is 9,919%. The positive Influence means if the education and training, the Automotive Engineering Teachers Association and also the job experience are improved, the teachersâ€™ professionalism can also be improved, and that happens otherwise.